2021
DOI: 10.1136/bjophthalmol-2020-318408
|View full text |Cite
|
Sign up to set email alerts
|

Avoiding mask-related artefacts in visual field tests during the COVID-19 pandemic

Abstract: AimsTo assess visual field (VF) pseudoprogression related to face mask use.MethodsWe reviewed a total of 307 VFs performed with a face mask (FPP2/KN95 or surgical masks) and compared them with prior VFs, performed before the pandemic. VFs with suspected pseudoprogression due to mask artefacts (VF test 1) were repeated with a surgical mask and an adhesive tape on its superior border (VF test 2) to distinguish from true VF loss. Several parameters including reliability indices, test duration, VF index (VFI), mea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(10 citation statements)
references
References 12 publications
(13 reference statements)
0
10
0
Order By: Relevance
“…30 As alluded to earlier, several studies have shown that fogging may result in unreliable VF testing and induced glaucoma-like artifacts because of obstructing patients' vision, which leads to inconsistent VF responses. [2][3][4][5] Alternatively, fogging may not increase the area of artifacts nor affect vessel density measurements in OCT-A imaging. This is probably because of differences with each technique; VF is a subjective measure of central and peripheral vision, whereas OCT-A is an objective measure of vessel density and does not depend on patients' responses.…”
Section: Discussionmentioning
confidence: 99%
“…30 As alluded to earlier, several studies have shown that fogging may result in unreliable VF testing and induced glaucoma-like artifacts because of obstructing patients' vision, which leads to inconsistent VF responses. [2][3][4][5] Alternatively, fogging may not increase the area of artifacts nor affect vessel density measurements in OCT-A imaging. This is probably because of differences with each technique; VF is a subjective measure of central and peripheral vision, whereas OCT-A is an objective measure of vessel density and does not depend on patients' responses.…”
Section: Discussionmentioning
confidence: 99%
“…Mask artefacts can occur, especially in the inferior field, and have a significantly increased rate of fixation losses. 5 It is proposed the most likely reason for artefacts is the breath exhaled through the superior border of the mask, resulting in fogging of the perimeter's trial lens. This can be reduced with adhesive tape covering the superior border of the mask.…”
Section: Practice In the Covid Eramentioning
confidence: 99%
“…It is proposed the most likely reason for artefacts is the breath exhaled through the superior border of the mask, resulting in fogging of the perimeter's trial lens. This can be reduced with adhesive tape covering the superior border of the mask 5 . It is also important to note real progression of the field due to glaucoma is not dismissed as a mask artefact and that a repeat field in combination with OCT of the nerve fibre and ganglion cell layers be performed.…”
Section: Practice In the Covid Eramentioning
confidence: 99%
See 1 more Smart Citation
“…Periodical awareness and constant reinforcements can prevent both aerosol-mediated infections and mask-induced artifacts from bowl-type perimetry. [ 10 ] However, for the time being, it seems appropriate to use an enclosed chamber perimeter for assessing glaucoma patients, at least until the pandemic gets over, for erroneous mask wearers or for patients who have mask intolerance while performing visual fields.…”
mentioning
confidence: 99%